PENINGKATAN KETERAMPILAN DESAIN GRAFIS BAGI MAHASISWA AISKA UNIVERSITY DALAM MENGHADAPI ERA 4.0: IMPROVING GRAPHIC DESIGN SKILLS FOR AISKA UNIVERSITY STUDENTS IN ERA 4.0 - Irfan Sadida; M. Gunawan Setyadi; Aisyah Mutia Dawis (Universitas Muhammadiyah Manado, 2022)
The rapid development of technology is very influential on institutions, society and even universities. At this time, the role of graphic design in all fields is needed. This can be proven by the many fields of business that utilize the expertise of graphic designers. The shifting habit of using digital media in human activities has made the use of design as media promotion increasingly widespread in the business world. Examples of promotional media include brochures, leaflets, posters, business cards, billboards, banners, and banners. This illustrates that graphic design skills are important things that students need to have in this modern era. Therefore, it is important to hold graphic design training as an initial means for students to improve their ability to produce a quality graphic design work.